Exercise-based Cardiac Rehabilitation in Coronary Disease: Training Impulse or Modalities? - Leprêtre, P.-M; Ghannem, M.; Bulvestre, M.; Ahmaidi, S.; Delanaud, S.; Weissland, T.; Lopes, P. (International Journal of Sports Medicine, 2016)
To compare the effects of 2 short programs with similar training load (TL), based on combined aerobic – resistance training (CT) or aerobic training (AT) on cardiorespiratory responses, 32 patients with coronary heart disease (CHD: 63.8±8.0y, 1.73±0.06 m, 84.8±15.9 kg, Left Ventricular Ejection Fraction: 0.53±0.8) performed 4 weeks of exercise rehabilitation based on CT (n=16) or AT (n=16). Maximal tolerated power (MTP), peak values of oxygen uptake (VO2peak) and heart rate (HRpeak), anaerobic threshold (VT1) were determined during an incremental cycling exercise test before and after training periods. TL, quantified using the session rating of perceived exertion, did not differ between both modalities (CT: 4 438±572 vs. AT: 4 346±592 AU, p=0.300). Improvements in VO2peak were larger after CT (+36.4±24.7% of pre-training VO2peak, i. e., +4.4±2.3 mL.min−1.kg−1, n=14) than observed after AT (+20.1±9.1% of pre-training VO2peak, i. e., +2.6±1.0 mL.min−1.kg−1, n=12) (p=0.014). Additionally, CT significantly improved power (54.6±23.8 vs. 75.1±21.2 watts, p=0.001) and VO2 associated at VT1 (VO2: 9.8±2.5 vs. 12.6±2.9 mL.min−1.kg−1, p=0.001). This might be taken into account when prescribing exercise rehabilitation for CHD patients with different initial clinical limitations.
Keywords: rating exertion perception; training load; heart disease; VO2peak; exercise capacity